Relative Rates of Gluten Digestion by Nine Commercial Dietary Digestive Supplements - Tanner, Gregory John (Frontiers in Nutrition, 2021)
Endopeptidases containing supplements may digest gluten and reduce the impact on celiac and gluten-sensitive subjects who inadvertently consume gluten. We investigated the relative rate of disappearance of coeliac relevant epitopes in extracts of nine commercial supplements, using two competitive enzyme-linked immunosorbent assays (ELISAs)—Ridascreen (detects QQPFP, QQQFP, LQPFP, and QLPFP) and Gluten-Tec (detects Glia-α20 and PFRPQQPYPQ). All epitopes are destroyed by cleavage after P and Q amino acids. Rates at pH 3.5 and pH 7.0 were measured. These experiments were designed to measure relative rates of epitope digestion not to mimic in vivo digestion. The supplements were: 1 GluteGuard, 2 GlutenBlock, 3 GliadinX, 4 GlutnGo, 5 GlutenRescue, 6 Eat E-Z Gluten+, 7 Glutenease, 8 Glutezyme, and 9 Gluten Digest. The mean initial rate and half-lives of epitope digestion were deduced and extrapolated to rates at the recommended dose of one supplement in a fasting stomach volume. At pH 7, supplement 1 was the fastest acting of the supplements, with Ridascreen ELISA, more than twice as fast as the next fastest supplements, 5, 6, 7, and 8. Supplements 2, 3, and 4 showed little activity at pH 7.0. Supplement 1 was also the fastest acting at pH 7 with Gluten-Tec ELISA, more than three times the rate for supplements 2 and 3, with supplements 4–9 showing minimal activity. At pH 3.5, supplement 1 acted more than five times as fast as the next fastest supplements, 2 and 3, when measured by Ridascreen, but supplements 2 and 3 were over two times faster than supplement 1 when measured by Gluten-Tec. Supplements 4–9 demonstrated minimal activity at pH 3.5 with either ELISA. Supplement 1 most rapidly digested the key immuno-reactive gluten epitopes identified by the R5 antibody in the Codex-approved competitive Ridascreen ELISA method and associated with the pathology of celiac disease.